The process of musical teaching-learning in the Camerata Reference Group of Plucked Strings of the Guri Project - Almeida, Lucas Ignacio; Morato, Cíntia Thais (Seven Editora, 2023)
This article presents the results of an academic research focused on the teaching-learning process in the rehearsals of the Camerata Reference Group of Plucked Strings of the Guri Project - ACIF Franca, SP. The general objective was to understand how the musical teaching-learning process occurs in this Reference Group (RG). The specific objectives were: to know how the structure and organization of the rehearsals of the GR Camerata of Plucked Strings (CCD) impact on the musical teaching-learning process; learn how CCD students learn music; understand how the social relationships established by the students participating in the CCD enhance their musical learning. Data were collected with the help of the Field Diary, through the observation of six CCD trials, which took place in Franca, SP, between May 3 and September 6, 2019. They were analyzed and categorized according to the specific objectives established. The results showed that the process of musical teaching-learning in the CCD is provided by the social relations that occur not only in the institutionalized times of the rehearsal, but also before its beginning and in the interval. It was observed that the students were guided by the sound result of the group and visually observing the body gestures of their colleagues, which constituted tricks for musical reading solutions or instrumental technique. The relationships established among the members of the CCD potentiated socio-musical interactions between the students, the conductor-educator and the area coordinators who sometimes visited the group. Despite some observed conflicts, these interactions allowed them to (re)recognize the experiences and abilities of the other, and this strengthened the students' engagement in group musical practice. DOI:https://doi.org/10.56238/chaandieducasc-024